Pelatihan Kompres Tepid Sponge Sebagai Upaya Menurunkan Demam Pada Anak Di Posyandu - Mohammad Ali Hamid (Journal of Community Development, 2022)
Health problems in partners include the high incidence of fever in toddlers which reaches 45.8%. Factors that affect the frequency of children getting sick are the tropics, where tropical areas like Indonesia are good for germs to breed, for example flu, malaria, dengue fever, and diarrhea. These various diseases are usually more prevalent in the transitional season. High fever can cause seizures which in this case are called febrile seizures. A febrile seizure is an emergency in children that must be treated immediately. One of the first aids is with a warm tepid sponge compress. The method used is health education with lectures, group discussions and workshops on tepid sponge compresses. As for what has been done: (1) draw up an activity plan, implementation schedule, technical instructions, supporting facilities and media, (2) hold training on tepid sponge compresses. After training, workshops, and mentoring were held, posyandu cadres and women of childbearing age at Posyandu partners in Wirowongso Village, 80% had knowledge of the Tepid Sponge Good compress and 20% had sufficient knowledge while those who had less knowledge did not exist. Women of childbearing age before and after training, workshops, and mentoring with a p value of 0.003. This shows that the knowledge of Posyandu cadres and women of childbearing age has been able to provide an analysis of the fever problems experienced by children and how to prevent and early management of the problems experienced. The psychomotor abilities of posyandu cadres and women of childbearing age at the Posyandu partners in Wirowongso Village in doing the Tepid Sponge compress are good and able to do it correctly.